Augmented Reality untuk Video Stereoscopic Pencak Silat - Citra Devi Murdaningtyas; Firza Nugra Satriaputra; Novita Astin (JST (Jurnal Sains Terapan), 2021)
There are many kinds of martial arts in Indonesia, both native martial arts from Indonesia such as pencak silat to various imported products from other countries such as karate, judo to capoeira. There are many pencak silat college, both in Indonesia and even around the world. One of the most influential martial arts in the history of Indonesian pencak silat is Tapak Suci. Based on survey data to the general public in Indonesia, out of 53 respondents there are only 20 respondents who know the pencak silat Tapak Suci, besides that only 3 respondents know the difference between Pencak Silat Tapak Suci and other martial arts, this is also reinforced by data from respondents who know that the Champ Light Tapak Suci team is only 5.7%. From these problems, a solution was made in the form of "AUGMENTED REALITY FOR PENCAK SILAT STEOROSCOPIC VIDEO". Augmented Reality can be used by many people because it utilizes Instagram filter technology as an Augmented Reality scan tool. This Augmented Reality content will later display a short video with the Steoroscopic Video technique about the education of the pencak silat tapak suci.